(untitled) (Raparin Journal of Humanities (RJH), 2020)
This study aims to explain the role and impact of news websites in Iraqi Kurdistan region in raising public awareness regarding the dimensions of national security and providing them with important information. In this study the method of content analysis is used to analyzing the news content in (Xendan) website and (K24) website during their coverage of the war on Islamic state. The most important finding in this study are: news websites concerned with different dimensions of national security and the military dimension has received more attention than other dimension.